Konsumsi Buah dan Sayur Siswa Sekolah Dasar Penerima Program Gizi Anak Sekolah di Cianjur - Tiurma Sinaga; Anna Vipta Resti Mauludyani; Haiva Nopiany; Marestry Nuzul Annur (Analisis Kebijakan Pertanian, 2019)
In recent 10 years, Indonesia has experienced chronic nutrition problems in terms of stunting. Almost all people aged older than five years had inadequate vegetables and fruits consumption. The nutrition program for school children (PROGAS) provided breakfast in many schools, particularly those with high stunting prevalence. The study aimed to analyze the fruits and vegetable consumption of elementary school children participating in PROGAS in Cianjur. This cross-sectional study was conducted to 61 students grade 5 and 6  in Public Elementary School Pamoyanan, Cianjur District. This study was done on March-August 2018. Data were collected by interview using a questionnaire, 2x24 hour food recall, and anthropometric measurement. The results of this study indicated that very few (1.6%, 8.2%, and 1.6%) respondents had adequate consumption of staple food, protein source, and fruits, respectively. There was no respondent consumed an adequate amount of vegetables. Staple food was significantly consumed more during the holidays rather than on school days (p=0.035). Fruits consumption was significantly higher during school days compared to holidays (p=0.001). Vegetable consumption was also consumed more during the school day. PROGAS provided a quite large contribution to the nutrient intake so that PROGAS should be continued with a higher amount of vegetables in the menu. AbstrakDalam waktu sepuluh tahun terakhir, Indonesia menghadapi permasalahan gizi kronis pada anak usia sekolah berupa stunting. Hampir seluruh penduduk usia di atas lima tahun kurang mengonsumsi sayur dan buah. Program Gizi Anak Sekolah (PROGAS) memberikan sarapan di berbagai sekolah, khususnya yang memiliki prevalensi stunting tinggi. Tujuan penelitian ini adalah menganalisis konsumsi buah dan sayur siswa SD penerima PROGAS di Kabupaten Cianjur. Desain penelitian menggunakan cross sectional study dengan 61 responden kelas lima dan enam Sekolah Dasar Negeri Pamoyanan, Kabupaten Cianjur. Penelitian dilaksanakan pada bulan Maret-Agustus 2018. Data diperoleh dengan wawancara menggunakan kuesioner, 2x24 jam food recall dan pengukuran antropometri. Sebagian kecil responden mengonsumsi cukup makanan pokok, lauk pauk, dan buah, secara berturut-turut sebesar 1,6%; 8,2%; dan 1.6%. Tidak ada responden mengonsumsi cukup sayur. Makanan pokok secara signifikan lebih banyak dikonsumsi selama liburan daripada hari sekolah (p = 0,035). Konsumsi buah signifikan pada hari sekolah dibandingkan hari libur (p = 0,001). Konsumsi sayur juga cenderung lebih tinggi di hari sekolah. PROGAS memiliki kontribusi yang cukup besar terhadap kecukupan gizi responden, sehingga PROGAS perlu dipertahankan dengan penambahan penyediaan sayur dalam menunya.